The correlation between stunting with development of toddler of 24-60 months - Faaza Rohma Fathia; Dyah Noviawati Setya Arum; Ana Kurniati (Jurnal Kesehatan Ibu dan Anak, 2019)
Background : Stunting is a problem that is being the focus of the government in Indonesia to be handled. Stunting is a result of chronic malnutrition which causes various long-term and short-term problems. If it occurs in stunting children, it can cause developmental disorders including subtle movements, rough motion, speech and language, and social independence. In Yogyakarta the highest incidence of stunting was in Gunungkidul Regency in the working area of ??the Puskesmas Gedangsari II. This study examines whether there was a correlation between stunting and the development of children aged 24-60 months. Objective : To determine the correlation between stunting and the development of children aged 24-60 months in the working area of ?Puskesmas ?Gedangsari II, Gunungkidul Regency in 2019. Methods : This study was an analytic observational study with a cross-sectional design. The population of this study were children aged 24-60 months and their mothers who came to the Posyandu in the working area of ??the Puskesmas Gedangsari II with a total of 52 samples that met the criteria. The instrument used was KPSP (Pre Screening Development Questionnaire) according to the age of the child. Analysis of univariable and bivariable data that used chi-square with significance level p <0.05 and 95% CI. Results : Based on the results of the bivariable analysis showed a correlation between stunting and the development of children aged 24-60 months (p = 0.017). Conclusion : There was a correlation between stunting and the development of children aged 24-60 months in the working area of Puskesmas ??Gedangsari II, Gunungkidul Regency.